Grappa quality from the Chianti and Montepulciano areas (Tuscany, Italy): monitoring the leaching of copper from distillation columns. (29th January 2018) - Tamasi, Gabriella; Donati, Alessandro; Leone, Gemma; Magnani, Agnese; Cini, Renzo; Macchia, Eugenio; Rossi, Claudio; Bonechi, Claudia
Summary: The main aim of this work was to evaluate the leaching of copper in grappa from distillation plant that treats Cabernet and Sangiovese marcs (Montepulciano and Chianti, Tuscany). Copper content (determined by atomic absorption spectrometry, AAS) was 1.05 ± 0.03 mg L −1 in industrial distillates (Cabernet marc, 82.3% alcohol, v/v), and 3.7 ± 0.2 μg L −1 in artificial grappa (62.0%, Cabernet) obtained by distilling marc in a laboratory‐scale glassware plant. The artificial grappa distillate was refluxed over copper shavings, and copper content, CCu, was analysed in relation to reflux time and wear of the copper bell. The results showed that CCu trend was almost linear with increasing alcohol concentration and constant reflux time, and vice versa . The ratios of selected volatile components were not influenced by reflux on the shavings. Abstract : This study reports on the study of copper release from Cu‐surfaces of industrial distillation plants, into grape marc distillate (Grappa). The tuning of distillate/Cu‐surfaces contact time and influence of alcohol contents, and pH, in distillation processes for Grappa are also reported.